Effect of acidic and alkali shocks on expression of efaA gene in Enterococcus faecalis, isolated from root canal infection - Beomidehagh, Mahsa; Rezaee, Mohammad Ahangarzadeh; Ganbarov, Khudaverdi; Jafari, Farnaz; Hasani, Alka; Alizadeh, Naser; Tanomand, Asghar; Kafil, Hossein Samadi (Cellular and Molecular Biology, 2018)
Enterococcus faecalis is an important opportunistic infectious agent involving the oral cavity and endodontics. The aim of this study was to evaluate the expression ratio of efaA gene in biofilm producer E. faecalis before and after receiving acidic and alkali shocks. One hundred E. faecalis isolates were gathered from 170 infectious root canals. After analysis of biofilm formation by the Microtiterplate method, the presence of efaA gene was examined by PCR and its expression was evaluated by Real-time PCR, one before applying any stressed to isolates and another by applying acidic and alkali shock. Chi-square method was used for statistical analysis. Eighty-two percent of samples had efaA gene. Evaluation of biofilm formation, 49% of the isolates were strong biofilm producer, 42% moderate and 10 % of them had no biofilm. 59% overexpression of efaA gene was observed in biofilm producer isolates, while there were no significant changes in samples with acidic stress and decreased expression after alkali shock. Findings of the present study, indicates importance of efaA gene in biofilm formation and pathogenesis of E. faecalis. Acid had no effect of expression of this gene but alkali reduced expression of this gene in a significant level. These results indicate the importance of efaA and acidic conditions in biofilm production by E. faecalis.